Narrativas de alunos universitários sobre o professor surdo e o ensino de libras - Klimsa, Bernardo Luis Torres (2013)
This dissertation is the result of the research developed during the Master course of Language Sciences, to the degree of master. The aim of this study is analyze the hearing students narratives about deaf teacher and Brazilian sign language teaching in university. In more specific level, we intend to: reflect on the teaching and learning of a second language as well as the main theories and their applicability to the context of Libras in university according to law; map the formation of teachers in university, discussing issues about profile of Libras teacher for teaching this discipline, didactic and methodological features most used by the teacher in teaching the language. To this end, we used a qualitative methodology, and as a research tool we chose to use an interview that provided reports of ten (10) university students who attended Libras course from both chosen institutions, in the city of Recife and Olinda. The results provided through the reports were categorized and then analyzed in the light of the theoretical framework proposed by content analysis. The results indicated a very favorable context in relation to the presence of deaf teacher, although at baseline it has caused some fear in students who thought the learning of Libras could not occur. Our expectation is that providing such data, new reflections may unfold thereby helping to expand the debate on this theme.